-3(x+8)+3=11(x-7)

Simple and best practice solution for -3(x+8)+3=11(x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x+8)+3=11(x-7) equation:


Simplifying
-3(x + 8) + 3 = 11(x + -7)

Reorder the terms:
-3(8 + x) + 3 = 11(x + -7)
(8 * -3 + x * -3) + 3 = 11(x + -7)
(-24 + -3x) + 3 = 11(x + -7)

Reorder the terms:
-24 + 3 + -3x = 11(x + -7)

Combine like terms: -24 + 3 = -21
-21 + -3x = 11(x + -7)

Reorder the terms:
-21 + -3x = 11(-7 + x)
-21 + -3x = (-7 * 11 + x * 11)
-21 + -3x = (-77 + 11x)

Solving
-21 + -3x = -77 + 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.
-21 + -3x + -11x = -77 + 11x + -11x

Combine like terms: -3x + -11x = -14x
-21 + -14x = -77 + 11x + -11x

Combine like terms: 11x + -11x = 0
-21 + -14x = -77 + 0
-21 + -14x = -77

Add '21' to each side of the equation.
-21 + 21 + -14x = -77 + 21

Combine like terms: -21 + 21 = 0
0 + -14x = -77 + 21
-14x = -77 + 21

Combine like terms: -77 + 21 = -56
-14x = -56

Divide each side by '-14'.
x = 4

Simplifying
x = 4

See similar equations:

| 13-6x+14= | | X^2+60x-252=0 | | 180-3x=12x | | x(x^2-4x+75)=0 | | F(x)=4x^9 | | 8.1+9=5.1x-3 | | zi+z+1+3i=0 | | 24X+1.19=.79 | | 51=4w-17 | | 47=2u+13 | | 24X+0.79=1.19 | | -7x+2y=9fory | | x+14=4x-9 | | 2(x+3)-x+4=2(x-1)+5 | | 5u+15=60 | | 9x=4x-8+2 | | -7x+2y=9foru | | i*z+z+1+3*i=0 | | (5x-12)=2 | | 8ty=4 | | -5x^2-30x-3=0 | | z*i+z+1+3*i=0 | | 2x^2+12x-19=8-3x | | 7A=8U | | 4y+12=-8y-4+10x | | s+7s= | | 7A+64=8U | | 3x^2+6x-3=7-7x | | x+310=410 | | 8x+6+5x+18=180 | | 2(y-3)=2x+4 | | b-5=1 |

Equations solver categories